Phyto-Pharmacognostical Standardization with HPTLC Fingerprinting of Root of Citraka (Plumbago zeylanica L.) - Akhilraj A.R,; Rukmini S,; Amalraj A.R, (International Journal of Ayurveda and Pharma Research, 2021)
Background: Citraka or Sveta Citraka (Plumbago zeylanica L.) is an important medicinal plant mentioned in Ayurvedic classics, belongs to the family Plumbaginaceae. The root of the plant exhibits medicinal properties. It has a broad range of pharmacological activities, including anti-inflammatory, antibacterial, antifungal, anticancer, antidiabetic, antioxidant, hepatoprotective, wound healing and cytotoxic.Objective: The aim of the study was to evaluate phyto-pharmacognostical standardization with HPTLC fingerprinting of root of P. zeylanica, one of the most accepted and beneficial medicinal plant in Ayurveda.Materials and Methods: P. zeylanica was collected from Konni, Kerala, India during the month of May 2018 and its root was studied for macroscopic, microscopic, physico-chemical, preliminary phytochemical screening and HPTLC fingerprinting following the standard protocol recommended by The Ayurvedic Pharmacopoeia of India and Quality Standards of Indian Medicinal Plants.Results: The root is long, stout, cylindrical and reddish to dark brown in colour. The transverse section of root showed 5-7 rows of small cubical or rectangular celled cork with light yellow walls, polygonal or slightly tangentially elongated cortex cells containing starch grains and coloured contents, phloem containing small groups of fibres, radially arranged xylem vessels and narrow, 1-4 seriate medullary rays. Physico-chemical analysis showed water soluble extractive value as 26.11±0.01 w/w and alcohol soluble extractive value as 15.85±0.00 w/w. Preliminary phytochemical analysis of root decoction showed the presence of alkaloids, carbohydrates, tannins, saponins, resin and quinones.Conclusion: The information obtained from this research work may be useful to establish the botanical as well as analytical standards for the root of P. zeylanica.